Psikologi Pendidikan Perspektif Ibnu Sina - Muhammad Zein Damanik (Yayasan Rahmat Islamiyah, 2022)
This article is written in order to construct Educational psychology in the perspective of Ibn Sina which is intended as a part of life. The type of writing in the article is qualitative research using library research with content analysis method as a data analysis tool. The description of the results of this article is the relationship between Soul and Body. That the human soul is a substance that can exist separately from the body.